Exploring the Science of Media and Messages in Health Communication in the Beverage Category: A Pandemic Alternative - Tanushikha Khichi, Dr. Sabyasachi Dasgupta (International Journal of Advanced Science and Technology, 2020)
Pandemic corona has paralyzed the world like never before. It is communication and healthy lifestyle that can protect humanity from such a disaster. This research is an exploration into effective messages and media alternatives that could affect human psyche and create deeper influence on buying healthy products. India is an ever-growing market for consumer goods. In the year 2015, Fast Moving Consumer Goods (FMCG) in India had generated revenues worth USD 47.3 billion. Overall, in the span of next four years, the market for FMCG is expected to rise at a CAGR of 20.6 per cent. It will expand to USD 103 billion. In the next decade, from 2015F to 2025F, the consumption in the rural market is expected to grow at CAGR 18.1 per cent. Concerns regarding health issues like obesity, chronic heart diseases, hypertension and diabetes have tremendously influenced people to make a shift in their consumption preferences. The communications delivered by different health drink brands are trying to educate the consumers to become health conscious thereby creating Unique Selling Propositions based on health messages and taglines. This research paper will try to explore the possibilities of health messages influences consumer decisions in purchase. Qualitative methodology with in-depth interview is used to explore deeper insights in terms of millennial buying behavior of the product and the implications of health messages. The study tries to analyse whether appropriate health messages would enable consumers purchase more of one brand than the other brand without the health messages.